Effect of constant heat flux on forced convective micropolar fluid flow over a surface of another quiescent fluid - Nurazleen, Abdul Majid; Nurul Farahain, Mohammad; Abdul Rahman, Mohd Kasim; Mohd Rijal, Ilias; Sharidan, Shafie (Horizon Research Publishing, 2019)
Due to the many applications of micropolar fluid such as blood, paint, body fluid, polymers, colloidal fluid and suspension fluid, it has become a prominent subject among the researchers. However, the characteristics of micropolar fluid flow over a surface of another quiescent fluid with heavier density of micropolar fluid under the effect of constant heat flux are still unknown. Therefore, the objective of the present work is to investigate numerically the forced convection of micropolar fluid flow over a surface of another quiescent fluid using constant heat flux boundary condition. In this study, the similarity transformation is used to reduce the boundary layer governing equations for mass, momentum, angular momentum and energy from partial differential equations to a system of nonlinear ordinary differential equations. This problem is solved numerically using shooting technique with Runge-Kutta-Gill method and implemented in Jupyter Notebook using Python 3 language. The behaviour of micropolar fluid in terms of velocity, skin friction, microrotation and temperature are analyzed and discussed. It is found that, the temperature is higher in constant wall temperature (CWT) compared to constant heat flux (CHF) at stretching or shrinking parameter and various micropolar parameter K. Furthermore, as Prandtl number increases, the temperature is decreasing in both CHF and CWT.